2011
DOI: 10.1371/journal.pone.0027394
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anticancer Activity of Gemcitabine in Combination with Noscapine via Antiangiogenic and Apoptotic Pathway against Non-Small Cell Lung Cancer

Abstract: BackgroundThe aim of this investigation was to evaluate the anticancer activity of Noscapine (Nos) and Gemcitabine (Gem) combination (NGC) against non-small cell lung cancer (NSCLC) and to elucidate the underlying mechanism of action.MethodsIsobolographic method was used to calculate combination index values from cytotoxicity data. In vitro antiangiogenic and apoptotic activity of Nos, Gem and NGC was evaluated. For in vivo studies, female athymic Nu/nu mice were xenografted with H460 tumors and the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 47 publications
(79 reference statements)
0
33
0
Order By: Relevance
“…Our laboratory and other researchers have provided evidence that enhanced tumor growth inhibition of various tumors was achieved by combining Nos with chemotherapeutic drugs [10,11,1720]. Further, our group also demonstrated previously that Nos enhances the anticancer activity of doxorubicin in a synergistic manner via inactivation of NF-kB and anti-angiogenic pathways while stimulating apoptosis against TNBC tumors [19]. …”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our laboratory and other researchers have provided evidence that enhanced tumor growth inhibition of various tumors was achieved by combining Nos with chemotherapeutic drugs [10,11,1720]. Further, our group also demonstrated previously that Nos enhances the anticancer activity of doxorubicin in a synergistic manner via inactivation of NF-kB and anti-angiogenic pathways while stimulating apoptosis against TNBC tumors [19]. …”
Section: Introductionmentioning
confidence: 77%
“…Several studies have suggested that Nos induces multiple proapoptotic responses that induce apoptosis against variety of cancer cells [9,14,15,18]. Previously, our lab also reported the synergistic activity between Nos with cisplatin and gemcitabine in A549 and H460 lung cancer cells [9,19]. The role of Nos as a sensitizer has also been shown by Sung et al (2010) who demonstrated that Nos (50 µM) significantly potentiated the cytotoxic and apoptotic effects of TNF, thalidomide, paclitaxel, and bortezomib in human leukemia KBM-5 cell lines by activating NF-κB [20].…”
Section: Discussionmentioning
confidence: 96%
“…1 Our laboratory is investigating newer combination therapies for lung cancer treatment. 30,31,32 One of the promising treatments for lung cancer are antiangiogenic agents that inhibit tumor growth, proliferation, and metastasis. 7,12 Several signaling molecules governing angiogenesis are of interest, including VEGF and PI3K.…”
Section: Discussionmentioning
confidence: 99%
“…We have selected human slow growing A549 adenocarcinoma cells and fast growing H460 large-cell carcinoma cells to evaluate the anticancer effect based on our previous studies. 30,31 The A549 and H460 NSCLC cells were obtained from American Type Culture Collection (Rockville, MD). A549 and H460 cells were grown in F12K and RPMI 1640 medium (Sigma Aldrich, St. Louis, MO) supplemented with 10% fetal bovine serum respectively.…”
Section: Methodsmentioning
confidence: 99%
“…IC 50 (drug) and IC 50 (citral) are concentrations of each compound when used alone to produce the same effect. CI values are interpreted as follows; CI41.3 antagonism; CI 1.1-1.3 moderate antagonism; CI 0.9-1.1 additive effect; CI 0.8-0.9 slight synergism; CI 0.6-0.8 moderate synergism; CI 0.4-0.6 synergism; CI 0.2-0.4 strong synergism; CI50.1 very strong synergism (Chougule et al, 2011).…”
Section: Combination Index Analysismentioning
confidence: 99%